KEDUDUKAN HUKUM APARATUR SIPIL NEGARA DILINGKUNGAN KEPOLISIAN NEGARA REPUBLIK INDONESIA - I Ketut Windia (Kerta Dyatmika, 2020)
Informants as connecting the tongue intel or the intelligence is very helpful in the process of seeking information in-depth (indepth information). The informant of the scope is broad, the above information indicates that the informant is not only in the governmental environment but also in another. It is very necessary for every entity that needs information, have informants done to be able to as information correction, know the enemy's power and activities that it does or as a shield for an entity to be free from threats facing him. The formulation of the issues raised in this research is how Regulations governing the legal protection of informants who assist the police in the investigation process and what are the legal safeguards against the informants who assist the police in the investigation process. This type of research is a normatof legal research moving from an informant required mobile in his job and is required to always standby in looking for news such as journalists only. Therefore, in the rules of intelligence the informant must be able to enter into, disguise as part of it. The risk is heavy. Dead or tortured by the parties investigated. This study uses an approach that examines the applicable legislation, legal theory, and can be the opinion of scholars related to the problems in this scientific paper is Legal Protection Against Informants Who Helped Police In Investigation. The conclusion of this research is the Regulation that regulate the legal protection of informants who assist the police in the investigation process is Law Number 13 Year 2006 concerning Protection of Witness and Victim namely Article 1 point 6 of the Law of Witness and Victim Protection is any effort to determine the right The right to provide assistance to provide a sense of security to witnesses and victims as well as informants that must be carried out by LPSK (Witness and Victim Protection Agency) or other institutions in accordance with the provisions of this law.Upaya legal protection of informants who assist the police in the process of investigation is now Has been issued Law no. Law No. 13 of 2006 concerning the protection of witnesses and victims, in the Law the forms of legal protection that can be given to witnesses or informants, among others by granting the right to the reporters provided for in Article 5 paragraph Keywords: Legal Protection, Informant, Police, Investigation